Agroecossistema de cultivo na fenologia de cultivares e potencial agronômico da amoreira-preta submetida a sistemas de poda em ambiente protegido - Trada, Tais Carine (2021)
Blackberry cultivation is traditionally carried out in the field. Production in a protected environment is a little-studied alternative, whose technology has the advantages of protecting against late frosts, hail damage, and avoiding the incidence of rain, which can cause diseases and harvest losses. The tested hypothesis of this work was that phenology is influenced by the cultivation environment, and the production differs between cultivars, influenced by the pruning system. The research aimed to evaluate the phenological behavior of blackberry in field cultivation and inside a protected environment and, the effects of pruning systems on production in a protected environment. The study was carried out at the Faculty of Agronomy and Veterinary Medicine (FAMV) from the University of Passo Fundo (UF), in Passo Fundo - RS/Brazil, during the 2020 harvest. The cultivars Tupy and BRS Xingu cultivated in the field and inside a protected environment were compared concerning phenological behavior and, in a protected environment, also the formation of secondary branches and production, once submitted to three pruning systems: a) DP1 - conduction of 3 stems with 1 pinching 15 cm after the last wire (1.90 m); DP2 - conduction of 3 stems with 2 pinchings at 0.8 m height and 15 cm after the last wire and; PD - drastic pruning and conduction of 3 stems with pinching 15 cm after the last wire. The experimental design occurred in randomized blocks, with treatments arranged in subdivided plots, with four replications and two plants per plot. The results showed that the protected environment condition provided a shorter duration of each phenological stage than in the field cultivation and, the ‘BRS Xingu’ cultivar presented stages of longer duration than ‘Tupy’ in both agroecosystems. The long duration characteristic of stages provided an overlap from up to five to six phenological stages in the same period. In a protected environment, greater formation of secondary branches was verified in 'Tupy' and, for both cultivars, pruning treatment with only 1 pinching 15 cm above the last wire was enough to induce a greater formation of these branches. On the other hand, the drastic pruning system delayed growth and thus the pinching, with a reduction in the emission of secondary branches and production. Without differing in terms of productivity, but because it presents fruits with higher average mass, lower TTA, and higher TSS/TTA ratio, it is concluded that 'Tupy' shows better agronomic performance than 'BRS Xingu'.